2019
DOI: 10.1002/mnfr.201800967
|View full text |Cite
|
Sign up to set email alerts
|

A Whole‐Grain Diet Increases Glucose‐Stimulated Insulin Secretion Independent of Gut Hormones in Adults at Risk for Type 2 Diabetes

Abstract: Introduction: The effect of whole-grain (WG) versus refined-grain (RG) diets on glucose-stimulated insulin secretion (GSIS) and β-cell function is unclear. Methods: In a double-blind crossover randomized controlled trial, 13 prediabetic adults (37.2 ± 1.8 y, BMI: 33.6 ± 1.4 kg m −2 , 2 h glucose: 146.9 ± 11.6 mg dL −1 ) are provided isocaloric-matched WG and RG diets for 8-weeks each, with an 8-10 week washout between diets. Glucose, insulin, and C-peptide are studied over 240 min following a 75 g OGTT. Incret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…Earlier clinical reports and recent clinical deep phenotyping in the RISE study in adults and youth in prediabetes or early T2DM indicate a large spectrum of insulin secretory capacity, basal insulin secretion, and glucose-stimulated insulin secretion responses, as well as heterogeneous responses to interventions with insulin replacement, weight loss, and exercise (43,44). Two recent studies provide clinical proof of concept that intervening at the behavioral level of MetS/prediabetes using short-term diet or exercise augments glucose-stimulated insulin secretion in human subjects (79,80). These studies support the idea that early intervention is critical to our ability to prevent or delay the progression to T2DM, but they also highlight the heterogeneity of these responses within different patients and the need to better understand particular islet compositions, β cell population compositions, and the respective responses of these heterogeneous cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier clinical reports and recent clinical deep phenotyping in the RISE study in adults and youth in prediabetes or early T2DM indicate a large spectrum of insulin secretory capacity, basal insulin secretion, and glucose-stimulated insulin secretion responses, as well as heterogeneous responses to interventions with insulin replacement, weight loss, and exercise (43,44). Two recent studies provide clinical proof of concept that intervening at the behavioral level of MetS/prediabetes using short-term diet or exercise augments glucose-stimulated insulin secretion in human subjects (79,80). These studies support the idea that early intervention is critical to our ability to prevent or delay the progression to T2DM, but they also highlight the heterogeneity of these responses within different patients and the need to better understand particular islet compositions, β cell population compositions, and the respective responses of these heterogeneous cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated whole grains to be superior to refined grains, with the most notable benefits being better glucose- and insulin-related parameters such as FPG, HbA1c, glucose metabolism, insulin level, insulin sensitivity as well as insulin resistance [ 19 , 23 , 57 ]. The rate of progression to T2DM and weight loss also demonstrated positive outcomes in favor of the whole grain group [ 57 , 77 ]. Furthermore, plasma inflammatory markers were also reduced in the study by de Mello et al [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty of 52 studies (57.7%) that investigated changes in weight and/or BMI, reported significant improvement postintervention [ 17 , 22 , 24 , 26 , 27 , 29 , 31 , 32 , 33 , 40 , 43 , 58 , 59 , 61 , 65 , 71 , 74 , 77 , 84 , 87 , 88 , 90 , 93 , 98 , 99 , 101 , 102 , 109 , 110 , 111 ]. Similar proportions of statistically significant findings were observed for the waist and hip circumferences and/or waist-to-hip ratio (17/32 studies, 53.1%) [ 17 , 18 , 24 , 26 , 32 , 33 , 38 , 58 , 61 , 62 , 84 , 87 , 88 , 101 , 102 , 108 , 109 ] as well as systolic and diastolic blood pressure (16/31 studies, 51.6%) [ 17 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-obese women had overall a higher HFII indicating a healthier diet compared to obese participants. They also consumed less snacks and more whole grain products, which have been suspected to improve the function of beta cells [ 21 ], and there was a trend toward lower consumption of red meats, generally associated with lower diabetes risk [ 22 ]. The HFII of non-obese women, however, was not associated with glycemic health 5 years postpartum.…”
Section: Discussionmentioning
confidence: 99%